(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In most cases, traffic accidents are accompanied by the braking process of the vehicle, so it seems that it is very important to study this issue and improve the accident investigation. The study of the braking process of a car is based on the determination of its deceleration depending on the coefficient of friction, based on the simplest physical laws.